COVID-19: A Psychological Pandemic amongst Health Workers and General Population - Pandit, Sanjib (Journal of Karnali Academy of Health Sciences, 2020)
It has been apparent that majority of population has been hit across the globe by this pandemic, both at the physical and mental level. As with the WHO’s declaration of corona virus outbreak to be pandemic starting march 2020, it has led to a situation of psychological pandemic as well. Looking to our context what have been apparent is that Health Workers and front-liners among others are facing the outbreaks with very limited resource while the country in itself is rumbled in the conflicts of politics and persistently poor health delivery system. Hence, the damage to the tolerance level whether be at psychological or at emotional level can be expected. Then this work of “vicarious traumatization” was found to be fascinating for the time being.1 The term was initially referred to as the mental symptoms experienced by psychotherapist by the psychological trauma owing to long interview and consultations with mentally ill persons.2 However, now it can be broadly used to define the distress and trauma following the cruel and post disastrous situation like this corona pandemic. Symptoms suggested as in the vicarious traumatization such as decreased appetite, sleep difficulties, fatigue, irritation, and fear have been reported by a majority of individuals.